Paradise Regained: An Apodictic Analysis of the Relationship Between School Size and Public Achievement - Arthur Coladarch (Journal of Research in Rural Education, 1983)
Approximately four score score and tweny years of research on the effects of institution size on pupil progress have produced only a literature of disagreement. Young theory builders seeking tenure and old administrators seeking guidance find no comfort in the conflicting conclusions and ambiguities. A critical examination of this confusing body of research, however, reveals evidentiary and inferential errors, naivite, intellectual puritanism, and rational extravagance. Revised and reinterpreted, this literature confesses a clear and near-unanimous finding: the smaller unit definitely is superior to the larger in pupil achievement. Two new studies add unnecessary confirmation; a startling afterthought will interest doctoral candidates seeking significant but painless dissertation topics.